Technologies and Catalysts for the Production of Polyethylene by Slurry Process: Patent Review - hossein bazgir; zahra Zahra Issaabadi (Baspārish, 2022)
For more than sixty years, thousands of patents and articles have been published annually on various manufacturing methods and comparing the properties and performance of manufactured polyethylenes. High-density polyethylene (HDPE) is one of the most widely used polyethylene in different grades, including pipes, films, fibers, bottles, etc., which about 50 million tons of this product is produced in slurry processes worldwide. Several technologies have been presented for the production of polyethylene in industrial plants. Each of these technologies has special operating conditions and type of catalyst and produces a specific product grade. High density polyethylene can be produced by gas phase or slurry. In this article, the processes and catalysts for the production of polyethylene in the slurry phase are reviewed.  These processes include Hostalen slurry process by Basell, CX slurry process by Mitsui, MarTECH process by Phillips, Innovene S process by Inoes, and Bostar process by Borealis. Hostalen and CX technology are similar in general terms and the main process, but they have differences that are discussed in this article. Commercialized catalysts used in the polyethylene production process, including TH series from Basell, RZ and PZ series from Mitsui, and BCH and BCE series from Sinopec, are also investigated.